Lectures du genre - Boisclair, Isabelle (Les éditions du remue-ménage, 2002)
Qu’en est-il du masculin et du féminin dans la production littéraire contemporaine? Que permettent d’apprendre sur les textes du passé les hypothèses actuelles quant au caractère culturel du dispositif de la différence des sexes? Autant de questions qui peuvent être soulevées au moment d’interroger les textes, en recourant aux notions de détermination et d’indétermination, de brouillage et de glissement du genre, qui sont reliées de près à celle de l’identité sexuelle. Chaque texte littéraire recèle une vision du genre sexuel et constitue à ce titre un lieu de médiation où il est possible de reproduire ce dispositif ou de le subvertir. Aborder la question du genre vient ouvrir, en quelque sorte, celle du féminin et poser, à ses côtés, celle du masculin, et, plus globalement, celle de la division du monde.
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; genre; identité sexuelle; identités LGBTQIA2+; lit3495; premier cycle; queer; thématiques; écriture des femmes*; études littéraires

Woman to woman: an everywoman's guide to lesbian sexuality - Booth, Carol (Simon & Schuster, 2002)
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques; états-unis

Queer globalizations: citizenship and the afterlife of colonialism - Cruz, Arnaldo; Manalansan, Martin F. (Sexual cultures, 2002)
Globalization has a taste for queer cultures. Whether in advertising, film, performance art, the internet, or in the political discourses of human rights in emerging democracies, queerness sells and the transnational circulation of peoples, identities and social movements that we call "globalization" can be liberating to the extent that it incorporates queer lives and cultures. From this perspective, globalization is seen as allowing the emergence of queer identities and cultures on a global scale. The essays in Queer Globalizations bring together scholars of postcolonial and lesbian and gay studies in order to examine from multiple perspectives the narratives that have sought to define globalization. In examining the tales that have been spun about globalization, these scholars have tried not only to assess the validity of the claims made for globalization, they have also attempted to identify the tactics and rhetorical strategies through which these claims and through which global circulation are constructed and operate.
Keywords: 1900-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; racisme; régions géographiques; sexualité; shm4000; système colonial; systèmes d'oppressions; thématiques; états-unis

Miroir bisexuel: une socio-anthropologie de l'invisible - Deschamps, Catherine (Modernes, 2002)
Les bisexuels, ça n'existe pas ! ". A-t-on déjà entendu proférer de tels propos sur les noirs, les blancs, les juifs, les femmes ou les gays ? Étrange démarche que de produire du sens au sujet d'une population dont la présence même est mise en doute. Mais la demande de preuve adressée aux femmes et aux hommes bisexuels a pour leurs émetteurs une fonction : les protéger des doutes identitaires qu'ils suscitent. Fondé sur l'observation de la seule association bisexuelle française ayant pignon sur rue, le présent ouvrage met l'accent en priorité sur les caractéristiques identitaires, politiques et culturelles. La bisexualité apparaît alors comme le terrain d'observation privilégié de l'ensemble des orientations sexuelles. Elle permet de la sorte une déconstruction des normes les plus insidieuses, communes à toutes et à tous. Car la bisexualité, plus une identité pertinente en elle-même, est une délatrice de l'invisible, qui ouvre, non plus à une approche diffractée de la différence, mais à une compréhension holistique du phénomène des sexualités.
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; corps; cours; discipline; discours dominant; europe; france; histoire et politique; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Integrating Disability, Transforming Feminist Theory - Garland-Thomson, Rosemarie (NWSA Journal, 2002)
This essay aims to amplify feminist theory by articulating and fostering feminist disability theory. It names feminist disability studies as an academic field of inquiry, describes work that is already underway, calls for needed study and sets an agenda for future work in feminist disability studies. Feminist disability theory augments the terms and confronts the limits of the ways we understand human diversity, the materiality of the body, multiculturalism, and the social formations that interpret bodily differences. The essay asserts that integrating disability as a category of analysis and a system of representation deepens, expands, and challenges feminist theory. To elaborate on these premises, the essay discusses four fundamental and interpenetrating domains of feminist theory: representation, the body, identity, and activism, suggesting some critical inquiries that considering disability can generate within these theoretical arenas.
Keywords: EDI; activisme; approches et analyses; corps; cours; discipline; militance; premier cycle; queer; ressource en ligne; santé; sciences humaines; sciences sociales; sex1920; thématiques; études critiques du handicap; études féministes

Life during wartime: Emotions and the development of act up - Gould, Deborah (Mobilization: An International Journal, 2002)
Focusing on the street AIDS activist movement ACT UP, this article explores the question of social movement sustainability. Emotions figure centrally in two ways. First, I argue that the emotion work of movements, largely ignored by scholars, is vital to their ability to develop and thrive over time. I investigate the ways AIDS activists nourished and extended an “emotional common sense” that was amenable to their brand of street activism, exploring, for example, the ways in which ACT UP marshaled grief and tethered it to anger; reoriented the object of gay pride away from community stoicism and toward gay sexual difference and militant activism; transformed the subject and object of shame from gay shame about homosexuality to government shame about its negligent response to AIDS; and gave birth to a new “queer” identity that joined the new emotional common sense, militant politics, and sexradicalism into a compelling package that helped to sustain the movement. Second, I investigate the emotions generated in the heat of the action that also helped the street AIDS activist movement flourish into the early 1990s.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; VIH; amériques; approches et analyses; identités LGBTQIA2+; militance; mouvements sociaux; périodes historiques; queer; ressource en ligne; régions géographiques; thématiques; émotions; états-unis

Femme/Butch family romances - Harris, Laura A. (Journal of Lesbian Studies, 2002)
My essay theorizes femme/butch family romances against the grain of dominant feminist and lesbian thought that desexualizes the space of mother/daughter desire. I do so through a reading/recoding of the infringing incestuous mommie-boy desires that surface in an archetypal lesbian novel, Jane Rule's Desert of the Heart.
Keywords: approches et analyses; arts; butch; discipline; genre; hétérosexisme; personnes lesbiennes; queer; ressource en ligne; systèmes d'oppressions; études littéraires

Le mouvement gai et lesbien américain face au SIDA - Marche, Guillaume (L'Homme & la Société, 2002)
Divided between essentialism and constructivism, the mobilization of united-statesian homosexuals becomes a real social movement when it goes beyond the opposition between integrationism and differentialism. Thanks to a complex identity forged by ACT-UP, it has been able in this way to resist AIDS. A comparison between San Francisco and New York shows that the initiative comes from the bottom up. Collective action is most effective as it takes account of differences (such as ethnicity) between homosexuals. This requirement has been dictated by the evolution of AIDS since the 1990s. It is, therefore, in stressing the subjectivity of the actors that the gay and lesbian movement can continue and contribute to social change in the United States.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; shm4000; systèmes d'oppressions; thématiques; états-unis

Pour un regard féministe matérialiste sur le queer. Échanges entre une féministe radicale et un homme anti-masculiniste - Masson, Sabine; Thiers-Vidal, Léo (Mouvements, 2002)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; féminisme matérialiste; philosophie politique; pol4212; premier cycle; périodes historiques; queer; sciences humaines; sociologie; thématiques

Sexualities : Sexualities and their futures - Plummer, Kenneth (Critical concepts in sociology, 2002)
Bringing together classic writings on sexuality from a social science perspective, this fascinating set covers topics including the history of the study of the area, theoretical approaches and issues of gender and sexuality. Volume four considers the wider issues around sexualities - addressing social change, postmodernity and the shifting of sexualities, and presenting an examination of the term 'queer'. An epilogue of suggested further reading is also included.
Keywords: approches et analyses; discipline; genre; postmodernisme; queer; sciences humaines; sexualité; sociologie; thématiques